Evaluation of Minimal Change Lesions Using Linked Color Imaging in Patients With Nonerosive Reflux Esophagitis. Issue 5 (13th May 2022) - Zhang, Ni-Na; Ma, Yi-Min; Sun, Qi; Shi, Liang-Liang; Xie, Yin; Zou, Xiao-Ping
Abstract : Background and Aims: High prevalence of minimal change lesion (MCL) in nonerosive reflux esophagitis (NERD) patients is commonly recognized by many endoscopists. However, it is difficult to detect MCL with conventional white-light imaging (WLI) endoscopy. Linked color imaging (LCI), a novel image-enhanced endoscopy technology with strong, unique color enhancement, is used for easy recognition of early gastric cancer and detection of Helicobacter pylori infection. The aim of the study was to compare the efficacy of LCI and WLI endoscopy in evaluating MCL in patients with NER. Materials and Methods: Forty-one patients with NERD and 38 subjects with nongastroesophageal reflux disease (non-GERD) were recruited in this study between August 2017 and July 2018. During upper gastrointestinal endoscopy, the distal 5 cm of the esophageal mucosal morphology at the squamocolumnar junction was visualized using WLI followed by LCI. MCL was defined as areas of erythema, blurring of the Z-line, friability, decreased vascularity, white turbid discoloration, and edema or accentuation of the mucosal folds. Three experienced endoscopists evaluated the color patterns for MCL on WLI images and on WLI combined with LCI images in both groups. A biopsy was taken 2 cm above the esophagogastric junction. Histologic slides were scored by a pathologist in a blinded manner. Results: The proportion of MCL was higher in the patients with NERD (70.7%, 29/41) than in patients with non-GERD (39.5%, 15/38) using WLI combined with LCI. In 12 patients with NERD, both WLI and LCI showed normal mucosa. The MCL detection rate was significantly higher when using WLI combined with LCI than when using WLI (70.7% vs. 51.2%, P =0.039) in patients with NERD. The histopathologic score of MCL (+) was significantly higher than that of MCL (−) patients in both the NERD group (4.59±0.32 vs. 2.36±0.34, P <0.01) and the non-GERD group (3.47±0.50 vs. 2.00±0.28, P <0.01). The intraobserver reproducibility levels and interobserver agreement were better with LCI than with WLI alone. Conclusions: Frequency of MCL was higher in patients with NERD than in those with non-GERD. MCL can be identified by using WLI combined with LCI in patients with NERD. By enhancing endoscopic images, LCI is more sensitive in detecting MCL compared with WLI.